KEDUDUKAN APARATUR SIPIL NEGARA WANITA SEBAGAI ISTERI KEDUA DALAM PERKAWINAN MENURUT HUKUM ISLAM DAN POSITIF - Khairilina Khairilina (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2019)
Arrangements regarding marriages for Civil Servants (PNS), in addition to being subject to Law Number 1 of 1974 concerning Marriage, must also comply with marital conditions regulated in Government Regulation Number 10 of 1983 concerning Marriage Licenses and Divorce for Civil Servants. Implicitly in Article 10 of Government Regulation Number 10 of 1983 concerning Marriage and Divorce Permits for Civil Servants, it is permissible for a husband (having the status of a civil servant) to marry more than one. But in Government Regulation No. 10 of 1983 jo. Government Regulation Number 45 of 1990 concerning Amendment to Government Regulation Number 10 of 1983 concerning Marriage and Divorce Permits for Civil Servants, especially in Article 4 paragraph (2), forbids a woman from being a Civil Servant to become the second / third / fourth wife, which is not stipulated in Law Number 1 of 1974 concerning Marriage. When making this policy, it was seen that the government's goal was to prevent a woman civil servant from having a harmonious domestic life, because there was a strong suspicion that if she became the second / third / fourth wife she would experience some complex household problems besides her husband and several other wives, who can cause obligations as servants of the state will be disrupted.PP No.45 of 1990 concerning civil service marriage licenses. Regarding polygamy, a woman who is a civil servant is prohibited from becoming a second wife. This is regulated in article 4 paragraph (2), if it violates the sanctions the dismissal is not respectfully as a civil servant (dismissal). But if a male civil servant wants to get married a second time and so on, it is not an important issue that he can fulfill the applicable provisions. Even if he is desperate to remarry even though the sanction is not permitted, it is only one of the most severe disciplinary penalties, in the indirect sense fired.